2017
DOI: 10.1007/s13337-017-0360-1
|View full text |Cite
|
Sign up to set email alerts
|

Inducible expression of magnesium protoporphyrin chelatase subunit I (CHLI)-amiRNA provides insights into cucumber mosaic virus Y satellite RNA-induced chlorosis symptoms

Abstract: Recent studies with Y satellite RNA (Y-sat) of cucumber mosaic virus have demonstrated that Y-sat modifies the disease symptoms in specific host plants through the silencing of the magnesium protoporphyrin chelatase I subunit (CHLI), which is directed by the Y-sat derived siRNA. Along with the development of peculiar yellow phenotypes, a drastic decrease in CHLI-transcripts and a higher accumulation of Y-sat derived siRNA were observed. To investigate the molecular mechanisms underlying the Y-sat-induced chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…We have previously generated two inducible silencing systems for CHLI and HSP90C in tobacco and found that the silencing of these genes could stimulate the plants to develop chlorosis [ 18 , 19 , 20 ]. As discussed previously [ 20 ], these systems have advantages over the experimental systems with the virus- or viroid-infected plants because, in these transgenic lines, it is possible to analyze those plant cells that have committed to developing but not exhibited chlorosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously generated two inducible silencing systems for CHLI and HSP90C in tobacco and found that the silencing of these genes could stimulate the plants to develop chlorosis [ 18 , 19 , 20 ]. As discussed previously [ 20 ], these systems have advantages over the experimental systems with the virus- or viroid-infected plants because, in these transgenic lines, it is possible to analyze those plant cells that have committed to developing but not exhibited chlorosis.…”
Section: Discussionmentioning
confidence: 99%
“…The siRNAs to peach latent mosaic viroid (PLMVd) lead the RNA silencing of two chloroplast protein genes: chloroplast heat-shock protein 90 (HSP90C) and a subunit of thylakoid translocase, resulting in intense chlorosis and yellow mosaic, respectively [ 16 , 17 ]. To investigate the precise mechanisms of chlorosis development, we generated two chlorosis model systems, in which a chemically inducible promoter drives the expression of RNAs silencing the expression of CHLI and HSP90C in transgenic tobacco plants [ 18 , 19 ]. In these models, the induction of RNA silencing of CHLI and HSP90C conditioned the declined expression of chloroplast protein genes, the upregulation of pathogenesis-related genes, and the significant reduction in chlorophyll contents that lead visible chlorosis [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the transcriptome changes above, downregulation of chloroplast and photosynthesis-related genes (CPRGs) or group 1 genes has been widely reported in symptomatic tissues of different combinations of host plants and viruses (Satoh et al ., 2010; Postnikova and Nemchinov, 2012; Mochizuki et al ., 2014; Zanardo et al ., 2019). Although it is natural that the expression of CPRGs is downregulated in chlorotic tissue, the present study, together with our previous results (Waliullah et al ., 2014, 2015; Bhor et al ., 2017 a , b ) strongly suggest that the CPRGs downregulation preceding visible chlorosis is the primary pathway of chlorosis development. The mechanism underlying the CPRGs downregulation may differ within pathosystems, but the present study suggests a possible involvement of retrograde signaling (RS) in chlorosis development induced by sub-viral pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that siRNA derived from Peach latent mosaic viroid (PLMVd) directs the RNA silencing of chloroplast heat-shock protein 90 (HSP90C) and consequently causes severe chlorosis or albinism (Navarro et al ., 2012). To analyze the molecular mechanisms of chlorosis induced by the RNA silencing of chloroplast proteins, we previously established experimental systems using chemically inducible promoter to drive RNAs to induce RNA silencing of CHLI and HSP90C in transgenic tobacco plants (Bhor et al ., 2017 a , b ).…”
Section: Introductionmentioning
confidence: 99%